Histone Methylation Is Required for Virulence, Conidiation, and Multi-Stress Resistance of Alternaria alternata - Meng, Shuai; Huang, Suya; Liu, Jinhua; Gai, Yunpeng; Li, Min; Duan, Shuo; Zhang, Shuting; Sun, Xuepeng; Yang, Qi; Wang, Yuchun; Xu, Kai; Ma, Haijie (Frontiers in Microbiology, 2022)
Histone methylation, which is critical for transcriptional regulation and various biological processes in eukaryotes, is a reversible dynamic process regulated by histone methyltransferases (HMTs) and histone demethylases (HDMs). This study determined the function of 5 HMTs (AaDot1, AaHMT1, AaHnrnp, AaSet1, AaSet2) and 1 HDMs (AaGhd2) in the phytopathogenic fungus Alternaria alternata by analyzing targeted gene deletion mutants. The vegetative growth, conidiation and pathogenicity of ∆AaSet1 and ∆AaSet2 were severely inhibited indicating that AaSet1 and AaSet2 play critical roles in cell development in A. alternata. Multiple stresses analysis revealed that both AaSet1 and AaSet2 were involved in the adaptation to cell wall interference agents and osmotic stress. Meanwhile, ∆AaSet1 and ∆AaSet2 displayed serious vegetative growth defects in sole carbon source medium, indicating that AaSet1 and AaSet2 play an important role in carbon source utilization. In addition, ∆AaSet2 colony displayed white in color, while the wild-type colony is dark brown, indicating AaSet2 is an essential gene for melanin biosynthesis in A. alternata. AaSet2 is required for the resistance to oxidative stress. On the other hand, all of ∆AaDot1, ∆AaHMT1, and ∆AaGhd2 mutants displayed wild-type phenotype in vegetative growth, multiple stresses resistance, pathogenicity, carbon source utilization, and melanin biosynthesis. To explore the regulatory mechanism of AaSet1 and AaSet2, RNA-seq of these mutants and wild-type strain was performed. Phenotypes mentioned above correlated well with the differentially expressed genes in ∆AaSet1 and ∆AaSet2 according to the KEGG and GO enrichment results. Overall, our study provides genetic evidence to define the central role of HMTs and HDMs in the pathological and biological functions of A. alternata.